Thermodynamic Behaviour of Hypersensitive Transitions Observed in Some Pr(III) Doped Systems - Verma, R.S.; Jain, Sushma; Joshi, G.K. (Asian Journal of Chemistry, 2010)
The saturated ligand environment produced by various ligands containing N, O donor atoms in 50% ethanol around Pr(III) ions, have been studied with respect to hypersensitive transitions involved in the system. The spectroscopic data for the hypersensitive transition have been correlated with the thermodynamic parameters, which yield the thermodynamic behaviour of the said transition. The -thermodynamic parameters include thermodynamic efficiency and partition function of the transition.